Digital image correlation, acoustic emission and in-situ microscopy in order to understand composite compression damage behavior. (15th February 2021) - Hamdi, Khalil; Moreau, Gurvan; Aboura, Zoheir
Abstract: In this work, a description of carbon fiber reinforced polymers (CFRP) compression-damaging scenario from first micro-damages to final failure of the material and potential effect of matrix (resin) on compressive mechanical properties and the damaging scenario is given. For that, two types of CFRP with the same woven reinforcement but with different resin were tested. First, combined load compression (CLC) tests were performed and the macroscopic compression behavior was then compared between the different materials. Then, analysis of the CLC testing with the multi-instrumentation was conducted to describe all the damage steps progression. Digital image correlation (DIC), acoustic emission (AE) and in-situ microscopy were the three parts of the multi-instrumentation. By combining the data from each technique, it was possible to verify the minor effect of the resin on the global compression behavior of composites. Signal processing tools (K-means and KNN) were used to cluster the acoustic emission signals. Three main classes were obtained and were labeled according to the possible damage scenario. This allowed the identification of the beginning of a severe damage (indicated by a noticeable rise in the measured acoustic energy) which was different depending on the matrix.